CONTROL OF THERMAL AND TECHNOLOGICAL PROCESS WITH DUE ACCOUNT OF THERMAL STRESSES - N. P. Voronova (Наука и техника)
The paper proposes a method for replacing constraints on phase variables with a constraint on control action. This method makes it possible to solve a problem pertaining to optimum quick heating of thermally massive body taking into account constraints on thermal stresses with the help of an analogous problem ignoring constraints on thermal stresses.